Navigating Ethical Dilemmas: A Comprehensive Review of Communication Ethics on Social Media - Kustiawan, Winda; Br Rambe, Suci Wahyu Tami; Karimah, Nur; Putra, Azrin Eka; Hasibuan, Qori Ananda Azhari; Hardi, Kuswoyo (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2023)
This comprehensive literature review navigates the ethical dilemmas surrounding communication on social media platforms. As technology continues to dominate various aspects of life in the current 5.0 era, social media has become a key driver of human activities. These platforms provide spaces for free and easy interaction, particularly among the youth, but also raise significant concerns regarding communication ethics. The widespread use of social media in Indonesia, despite ranking low in digital civility in Southeast Asia, poses challenges such as the increased spread of hoaxes, cyberbullying, and discriminatory behavior. With growing dependence on social media, especially among the youth, understanding the relationship between communication ethics and mental health becomes crucial. This article reviews literature on communication ethics in social media, emphasizing its impact on online civility, the mental health of the youth, and the ethical challenges in online communication in Indonesia. The findings suggest a need for policies promoting ethical communication on social media and increased awareness among the younger generation. The study advocates for educational initiatives focusing on sustaining and continuously applying communication ethics.